Delayed diagnosis of bilateral iatrogenic ureteric injury presenting with life-threatening pseudo-acute kidney injury after hysterectomy: a case report - Parisudha, Ryuu Damara; Brodjonegoro, Sakti Ronggowardhana; Wiratma , Made Kresna Yudhistira (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Bilateral ureteric injury after pelvic surgeries, particularly hysterectomy, carries a substantial risk of life-threatening conditions such as severe respiratory distress related to pseudo-acute kidney injury (pseudo-AKI) and sepsis due to peritonitis. A 47 y.o. woman presented with anuria 9 d after hysterectomy. She exhibited severe dyspnea requiring intubation, reduced level of consciousness, tachycardia and abdominal distension. Laboratory results revealed rapid increment of urea and creatinine post operatively requiring serial hemodialysis, leukocytosis, hyperkalemia and metabolic acidosis. Imaging identified bilateral hydronephrosis and ascites. An emergency laparotomy was performed, draining 2.7 L of intraperitoneal urine and revealing bilateral distal ureteral ligation with perforations. Subsequent bilateral ureteroneocystostomy was conducted resulting in significant improvements in clinical status as well as normalization of the renal function within 48 hr postoperatively. Bilateral iatrogenic ureteric injury with concurrent urinary ascites is an uncommon but serious complication of gynaecologic surgeries, particularly hysterectomies. This condition significantly increases the risk of renal failure and other life-threatening complications. Delayed diagnosis, as seen in this case, exacerbates these risks. Immediate surgical laparotomy with subsequent ureteroneocystostomy is critical for renal recovery and resolution of urinary ascites. Although rare, bilateral ureteric injury with urinary ascites necessitates prompt recognition and urgent surgical management to prevent severe renal impairment and other life-threatening outcomes. Careful preoperative planning and intraoperative ureteral visualization are essential in reducing the risk of such injuries.